PELUANG DAN TANTANGAN INSTITUSI PENDIDIKAN EKONOMI ISLAM DALAM KONTEKS TREND EKONOMI GLOBAL - Nur Kholis (Jurnal Ekonomi & Keuangan Islam, 2011)
The development of Islamic economy is currently very rapidly in Indonesia, particularly Islamic banking. Of course, this is due to start his conscious development of the community against the adverse effects of western capitalist economies. Even though, so the high growth of Islamic banking is not accompanied by high quality human resources. This paper tries to dig deeper into the role of institutions and educational institutions in preparing human resources "insani". Prepared with human resources are good then the sharia Islamic economy will be able to exist and grow amid a global economy.